Good Governance and Civil Service Reform in Egypt - Labib, Ahmed Atef (AUC Knowledge Fountain, 2022)
Governments in different states and even different governments within the same state may pursue different goals. To achieve their goals they apply administrative reforms, including civil service reforms, to adjust the government for achieving the intended goals. Pursuing different goals entails applying different administrative reforms. In the 2000s, the World Bank and the International Monetary Fund (IMF) suggested the Egyptian government, through loan conditionality, an administrative and civil service reform to promote economic growth based on their concept of good governance. In this paper, I argue that the suggested reform does not target economic growth but targets debt repayment. To demonstrate the contradiction between the suggested reform and the alleged goal, in the first chapter I review the history of civil service reform in Egypt from the time of Mohamed Ali Pasha until the suggested reforms by the World Bank and the IMF. This review shows that different Egyptian rulers reformed the civil service to play a certain role while the foreign creditors of the 19th century applied similar reforms to those of the international financial institutions to secure debt repayment. In the second chapter, I explain the role of the civil service according to the concept of good governance upon which the World Bank and the IMF suggested the administrative and civil service reform in Egypt. In the third chapter, I tackle the critique of the suggested civil service reform to show that its main goal is making savings to ensure debt repayment, not improving the civil service to perform the assigned role.